2020
DOI: 10.34256/ijpefs2012
|View full text |Cite
|
Sign up to set email alerts
|

Postural control in male ten-pin bowlers of different level of competitiveness

Abstract: Ten-pin bowling is considered a highly skilled recreational activity with players demonstrating various anthropometric and physiological characteristics. The purpose of the current study was to assess both static and dynamic body balance, in ten-pin bowlers of different level of competitiveness. Thirty four ten-pin bowlers who competed at a high (Level-A, n=17) and a lower level (Level-B, n=17) as well as eighteen individuals without experience in ten-pin bowling (Non-bowlers) participated in the study. Static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
0
0
Order By: Relevance
“…Meanwhile the body height and the minimum breadth of the hand) were found to be significantly correlated in the multiple regression model analysis. In accordance with the present results, previous studies have demonstrated that height [29,30,31], BMI [32,33,34] and the length and dimensions of the forearm, arm, and hands were significantly correlated with handgrip strength [35,36,37].…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile the body height and the minimum breadth of the hand) were found to be significantly correlated in the multiple regression model analysis. In accordance with the present results, previous studies have demonstrated that height [29,30,31], BMI [32,33,34] and the length and dimensions of the forearm, arm, and hands were significantly correlated with handgrip strength [35,36,37].…”
Section: Discussionsupporting
confidence: 93%
“…The literature on this topic is consistent with both the aforementioned study and our research findings. Stefopoulos et al (2020) conducted a study with male bowling athletes; their findings can serve as an example. These researchers examined athletes' postural control level and stated that the most important motor skills in bowling are dynamic balance, coordination, and hip flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria that present requirements for talent selection in the bowling discipline were determined through bilateral interviews with expert coaches affiliated with the Turkish Bocce, Bowling, and Dart Federation, as well as through studies conducted in the literature on the bowling discipline (Kirschenbaum et al 1982;Tan et al, 2000;Crust, 2007;Hon et al, 2009;Fuss, 2009;Abdollahipour et al, 2017;Stefopoulos et al, 2020;Petrie, 2020). In this context, as seen in Table 3, four main criteria and their corresponding sub-criteria were identified as the criteria to be used for talent selection in the bowling discipline.…”
Section: Determination Of Talent Criteria For the Bowling Disciplinementioning
confidence: 99%